Developing a software package for global desktop assessment of environmental flows - Smakhtin, Vladimir U.; Eriyagama, Nishadi (2008)
The paper describes a method and software package for desktop assessment of environmental flows - a hydrological regime designed to maintain a river in some agreed ecological condition. The method uses monthly flow data and is built around a flow duration curve, which ensures that elements of natural flow variability are preserved in the estimated environmental flow time series. The curve is calculated for several categories of aquatic ecosystem protection - from 'largely natural' to 'severely modified'. The corresponding environmental flows progressively reduce with the decreasing level of ecosystem protection. A non-linear data transformation procedure subsequently converts the calculated environmental flow duration curve into a continuous time series of environmental flows. The software has facilities to zoom on a river basin, calculate a variety of hydrological characteristics, define or select any category of ecosystem protection, calculate the associated environmental flow duration curves and time series and display both. The analyses can be carried out either using default (simulated) global flow data, with a spatial resolution of 0.5 degree, or a user- defined file. The package is seen as a training tool for water practitioners, policymakers and students, and as a tool for rapid preliminary environmental flow assessment.